Comparative genome analysis of Pasteurella multocida from Australian domestic animals suggests broad patterns of transmissions across multiple hosts and origins - Joanne L. Allen; Rhys N. Bushell; Amir H. Noormohammadi; Pam Whiteley; Susan A. Ballard; Mary Valcanis; Glenn F. Browning; Marc S. Marenda (PLoS ONE, 2025)
The zoonotic bacterium Pasteurella multocida infects a wide range of animals worldwide. While the genetic diversity of this pathogen is well described in production animals, it remains underexplored in companion animals. In Australia, most P. multocida genomes come from commercial poultry. Here, 59 P. multocida clinical isolates obtained from Australian pets, (cats, dogs, rabbits), farm animals (birds, ruminants, porcine) and captive wildlife (Quolls, Serval) between 2006 and 2023 were sequenced and compared to 523 representative RefSeq genomes. Clustering and phylogenomic analyses placed 24/25 Australian pet isolates in a long-branched clade containing several MLST profiles (ST36, ST37, ST171, ST359, ST451 and ST527) also found in human isolates. Genotypes associated with Australian production animals (e.g., ST8, ST9 and ST20 from poultry, ST79 and ST394 from cattle) fell in the main branch of the tree. Minimum spanning tree and SNP analyses suggested several occurrences of cross-species transmission. Mobile genetic elements were found across the P. multocida population, without clustering into any specific phylogenetic, host, or geographic group. However, a 1.8 kb cryptic plasmid (Acc. U51470), previously described in Pasteurella canis strains from South Korea, was detected in 99/289 (34.3%) Australian P. multocida isolates from various hosts, while being largely absent from the rest of the world. Antimicrobial resistance was not detected in the isolates from Australian companion animals and captive wildlife. However, resistances to tetracyclines in bovine isolates (2/10) and ampicillin in avian (1/17) isolates were identified. This study greatly expands our insights on the diversity of P. multocida genomes from Australian companion animals and provides the basis for wider investigations on the molecular epidemiology and diversity of this pathogen, with potential applications to better understand the zoonotic risks associated with this pathogen.